PENGARUH INFLUENCER MARKETING DAN VIRAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN BITTERSWEET BY NAJLA - Muhammad Miftahul Fathurrahman, (2021)
Bittersweet By Najla is known as a marketer who uses influencer marketing and viral marketing methods. Although this method is known as a powerful marketing method, sales of new products marketed using influencer marketing and viral marketing are not in line with the old products that people are familiar with. This study aims to prove the influence of influencer marketing on purchasing decisions and viral marketing on purchasing decisions. This research is a descriptive quantitative study with the object of research being Bittersweet By Najla consumers in Jabodetabek. The sample is 100 respondents with purposive sampling technique. This research hypothesis was tested using SmartPLS 3.0 with the results (1) There is a significant influence of influencer marketing on purchasing decisions of 0.425 (2) There is a significant influence of viral marketing on purchasing decisions of 0.346 (3) There is an influence of influencer marketing and viral marketing on purchasing decisions of 0.509.